The influence of different sources of polyphenols on submaximal cycling and time trial performance - Clifford, T.; Scott, A.; Mitchell, N. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The primary purpose of the study was to establish the effects of commercially available polyphenol-rich antioxidant supplements, Pycnogenol® with added bioflavonoids (PYC-B) compared to CherryActive (CHA), on 20-km cycling performance. Using a double-blind counterbalanced, repeated-measures design, - male cyclists or triathletes (32.1 ± 11.2 years; VO2max 4.2 ± 0.7 L/min; maximal power output 391.7 ± 39.5 W) consumed 200 mg of CHA, 120 mg of PYC-B, or 200 mg of placebo (PLA) capsules, 2 days before and on the day of each experimental trial. The experimental trials consisted of four 5-min stages at 40%, 50%, 60%, and 70% maximal power output (Wmax), followed by a 20-km time trial (TT). A two-way repeated-measures ANOVA revealed no significant differences between trials for heart rate (HR), respiratory exchange ratio (RER), gross mechanical efficiency (GME), oxygen consumption (VO2), or blood lactate (Blac) at any of the intensities completed during the initial 20-min phase of the trial (p > .05). Final 20-km TT times were not significantly different between trials (p = .115, eta-squared = .24), but, compared to PLA, PYC-B did result in a significantly faster completion of the final 1 km of the TT by 3.8 s (p = .033, ES = 0.62) and a significantly greater 6.2% power output over the final 5 km of the TT (p = .022, ES = 0.44). This study suggests that 3 days of supplementing with PYC-B could offer some benefits for cycling performance towards the end of an event when performance is likely to be compromised by accumulated free-radical damage.